An alterative effect by the tropical North Atlantic SST in intraseasonally varying El Niño teleconnection over the North Atlantic - Mi-Kyung Sung; Yoo-Geun Ham; Jong-Seong Kug; Soon-Il An (Tellus A: Dynamic Meteorology and Oceanography, 2013)
It is known that there is a distinct intraseasonal variation in wintertime atmospheric responses to El Niño over the North Atlantic, namely a positive North Atlantic Oscillation (NAO)-like response during early winter (November to December) and a negative NAO-like response during late winter (January to March). In this article, we suggest that the tropical North Atlantic (TNAL) sea surface temperatures (SSTs) significantly alter the North Atlantic atmospheric response to El Niño: the warm TNAL SST condition intensifies the negative NAO-like response and vice versa. During late El Niño winters, the TNAL SST tends to increase due to the atmospheric bridge between the tropical Pacific and the Atlantic oceans. The warm tendency in the TNAL SST can intensify the height contrast in the El Niño teleconnection between early and late winter. During early winter (when the response of the TNAL SST to El Niño has not been established yet), atmospheric circulation over the North Atlantic varies widely under various TNAL conditions. Consequently, the average influence of El Niño over the North Atlantic region becomes weaker in the early winter. By contrast, the overall warming over the TNAL region during the late El Niño winter is conducive to the formation of a negative NAO pattern. As a result, the climatic impact becomes stronger during the late winter.